Analysis of the Effectiveness of the Community Service Program in the Development of Sumber Padi Village, Batubara Regency - Harahap, Aninda Muliani; Nasution, Kevin Rasyid; Adsri, Muhammad Tauhid; Aidin, Winda; N, Nurhaliza (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This article analyzes the effectiveness of the Community Service Program (KKN) in Sumber Padi Village, Batubara Regency, conducted by Group 44 from the State Islamic University of North Sumatra. The urgency of this research lies in evaluating the sustainable impact of the KKN program on village development, with a focus on infrastructure, health, education, and the local economy. The methodology employed is qualitative descriptive with a case study approach, involving field observations, in-depth interviews, and document analysis. The findings reveal that KKN plays a significant role in improving the quality of life in the village through infrastructure development, economic empowerment, and enhancements in education and public health. KKN students act as agents of change, successfully introducing innovations and sustainable practices to the village. In conclusion, the participatory approach implemented in the KKN program has proven effective in promoting sustainable development in Sumber Padi Village and can serve as a model for similar programs in other regions.